The Association between LGBTQIA+ Self-Identification and Factors Facilitating Homelessness: A Scoping Review of the Occupational Therapy Peer-Reviewed Literature. Issue 2 (1st April 2021) - Gutman, Sharon A.; Precin, Pat; LaForest, Marian L.; Chu, Alison; Diaz, Maria; Engel, Rena; Epino, Katarina; Gotlieb, Rachel; Hart, Lara; Plaus, Nicole; Xing, Susan; Zimmer, Alana
Abstract: The purpose of this paper was to perform a scoping review examining the occupational therapy peer-reviewed literature regarding the LGBTQIA+ community to (a) determine what types of scholarship have been generated and (b) whether the association between LGBTQIA+ self-identification and homelessness has been identified and addressed in occupational therapy practice. A database search of seven peer-reviewed, health care publication indexes, with 19 key search terms was performed. The database search targeted articles published prior to January 2020. Fifty-three articles were identified within the occupational therapy literature and addressing the LGBTQIA+ community. The majority of this literature (n = 40) was exploratory studies through which researchers sought to better understand the unique needs of subgroups within the LGBTQIA+ community. Only three articles addressed the link between LGBTQIA+ self-identification and homelessness with no articles that addressed evaluation and intervention of the factors predisposing this population to homelessness. As occupational therapists have a unique skill set that could be used to help LGBTQIA+ community members transition from and remain free from homelessness, occupational therapy researchers must develop and assess interventions that target these factors. Occupational therapy educators should develop and assess curricular programming to heighten student comfort and preparedness in service delivery to this community.